2023
DOI: 10.1039/d3sm00896g
|View full text |Cite
|
Sign up to set email alerts
|

Salt induced micellization conduct in PEO–PPO–PEO-based block copolymers: a thermo-responsive approach

Nitumani Tripathi,
Debes Ray,
Vinod K. Aswal
et al.

Abstract: Effect of varied salts in inducing the structural morphology changes in L44 and F77 at 30 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…The l max of the oil orange SS in the micelles was determined to be 494 nm. 26,27 The results revealed that the amount of dye solubilized in the block copolymer micelles was higher than that in the random copolymers (Fig. 3a and b/Fig.…”
mentioning
confidence: 94%
“…The l max of the oil orange SS in the micelles was determined to be 494 nm. 26,27 The results revealed that the amount of dye solubilized in the block copolymer micelles was higher than that in the random copolymers (Fig. 3a and b/Fig.…”
mentioning
confidence: 94%
“…However, the introduction of salts modifies the specific area occupied by each phase within the system [16,[20][21][22]. For instance, the addition of ionic salts can reduce the solubility of Pluronic molecules in water and disrupt the micellar structure [23]. These modifications, intricately linked to the Hofmeister series but also to the specific ratio between the number of monomers in the poly(ethylene oxide) and poly(propylene oxide) blocks, establish a relationship between the behavior of ions as promoters or disruptors of water's structural stability, depending on their ability to remain hydrated [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These modifications, intricately linked to the Hofmeister series but also to the specific ratio between the number of monomers in the poly(ethylene oxide) and poly(propylene oxide) blocks, establish a relationship between the behavior of ions as promoters or disruptors of water's structural stability, depending on their ability to remain hydrated [22,24,25]. Such intricate correlations between ionic properties and phase changes within Pluronic solutions continue to foster further investigations to unravel the underlying mechanisms governing these complex systems [23,24,26]. This has revealed that some ions can interact with the polymer chains in a very specific way, leading to behavior that cannot be explained by the Hofmeister series [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Dyeresponsive magnetic NPs can be synthesized in an inexpensive way by using commercially available block polymers. Block polymer molecules adsorbed on the surface of tiny magnetic NPs create a huge surface area to extract large concentrations of dye from contaminated water through specific interactions 14,15 existing between the block polymer and dye molecules. An external magnetic field allows the removal of dye-loaded magnetic NPs, leaving behind pure water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dye-responsive magnetic NPs can be synthesized in an inexpensive way by using commercially available block polymers. Block polymer molecules adsorbed on the surface of tiny magnetic NPs create a huge surface area to extract large concentrations of dye from contaminated water through specific interactions , existing between the block polymer and dye molecules. An external magnetic field allows the removal of dye-loaded magnetic NPs, leaving behind pure water. The extraction depends on the molecular structure of the dye, which facilitates the solid–liquid interfacial adsorption of dye molecules usually governed by the surface activity as well as the polarity of the dye molecules .…”
Section: Introductionmentioning
confidence: 99%